Identifying the Beast: Samuel Horsley and the Problem of Papal AntiChrist - Robinson, Andrew (The journal of ecclesiastical history, 1992)
The tortuous history of apocalyptic speculation took a new turn in the late eighteenth century, and one of its proponents was the ebullient bishop of Rochester, Samuel Horsley. The new and alarming ideas emanating from abstruse considerations of the Book of Daniel, of Revelation and the eighteenth chapter of Isaiah were puzzled over in a series of reviews in the Gentleman's Magazine, one of which was a review of the letter from an anonymous ‘Country Clergyman’ to the bishop. It was clearly the opinion of the ‘Country Clergyman’ that Horsley's views were novel.